Explaining species richness from continents to communities: the time-for-speciation effect in emydid turtles - Stephens, Patrick R; Wiens, John J (The American naturalist, 2003)
Speciation is the process that ultimately generates species richness. However, the time required for speciation to build up diversity in a region is rarely considered as an explanation for patterns of species richness. We explored this "time-for-speciation effect" on patterns of species richness in emydid turtles. Emydids show a striking pattern of high species richness in eastern North America (especially the southeast) and low diversity in other regions. At the continental scale, species richness is positively correlated with the amount of time emydids have been present and speciating in each region, with eastern North America being the ancestral region. Within eastern North America, higher regional species richness in the southeast is associated with smaller geographic range sizes and not greater local species richness in southern communities. We suggest that these patterns of geographic range size variation and local and regional species richness in eastern North America are caused by glaciation, allopatric speciation, and the time-for-speciation effect. We propose that allopatric speciation can simultaneously decrease geographic range size and increase regional diversity without increasing local diversity and that geographic range size can determine the relationship between alpha, beta, and gamma diversity. The time-for-speciation effect may act through a variety of processes at different spatial scales to determine diverse patterns of species richness.